Development of Digital Learning Media Based on Folktales in Indonesian Language Learning for Fifth-Grade Students at UPT SD Negeri 2 Timoreng Panua - Sulistinayanti; Nuraini Kasman (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This research aims to develop and test the effectiveness of digital learning media based on folklore in teaching Indonesian language to fifth-grade students at UPT SD Negeri 2 Timoreng Panua. The background of this study lies in the pedagogical gap between conventional, passive teaching methods and the characteristics of students who are predominantly audio-visual and kinesthetic learners. Therefore, an interactive and context-based medium grounded in local wisdom is needed to enhance students’ engagement and literacy skills. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The product produced is an Interactive Learning Multimedia (ILM) based on local folklore, which was systematically developed and validated by experts. The validation results indicate a very high level of feasibility: material expert 92%, media expert 80%, and instructional expert 90%, with an overall category of “very feasible.” A limited trial involving 10 students showed an average gain score of 0.45, categorized as moderate effectiveness according to Hake’s criteria. Of these, 1 student had a low gain score (≤0.30), 9 students achieved moderate gain scores (0.30–0.70), and none were in the high category (>0.70). In the broader trial involving 30 students, the average gain score was 0.44, also categorized as moderate effectiveness. Among them, 7 students fell into the low category (g ≤ 0.30), 22 in the moderate category (0.30 < g ≤ 0.70), and 1 student (S-25) in the high category (g > 0.70). This indicates that most students experienced significant improvement after using the developed media. The student response questionnaire also showed high levels of attractiveness (4.6) and ease of use (4.2) on a 5-point scale. These findings demonstrate that the developed digital learning media based on folklore is valid, engaging, and effective in improving students’ literacy. Theoretically, this research reinforces the application of Mayer’s Multimedia Learning Theory and Bruner’s Constructivist Theory in primary education, while practically, it serves as an innovative model for integrating local wisdom into digital learning. Thus, this study contributes to the development of contextual, interactive, and culturally relevant learning media.